The global failure of facing the pandemic - Luis Eugenio Portela Fernandes de Souza; Marcia Caldas de Castro; Eduardo Hage Carmo; Maurício Polidoro (Taylor & Francis Group, 2022)
The COVID-19 pandemic outbreak in late 2019 has had social, political, and economic consequences worldwide. However, its emergence was not a surprise. In 2015, a Panel organised by the World Health Organization highlighted the importance of learning about the crisis caused by the Ebola epidemic. In 1992, the Committee on Emerging Microbial Threats to Health of the US Institute of Medicine warned of the possibility of an emerging global microbial threat. In this text, we point out five arguments that reveal the global failure in facing the pandemic: (1) deficiency in the global alert system and the fragility of the International Health Regulations (IHR-2005), (2) problems of the international response to the pandemic, related to global health governance, (3) the dispersed global adoption of the elimination strategy (zero Covid) widely seen as a policy of restriction of freedom instead as a strategy of inequities reduction, (4) fragile control of the disease with a narrow reading of the associated problems, and (5) global setbacks in achieving the Sustainable Development Goals in the context of ongoing neoliberal national policies. Finally, we argue that overcoming the weaknesses discussed requires strengthening health systems in all their components and expanding social welfare policies.